EMPLOYEE PERFORMANCE VIEWED FROM WORK DISCIPLINE, ORGANIZATIONAL CULTURE, AND COMMUNICATION (STUDY OF SOCIAL SERVICES IN WONOGIRI DISTRICT) - Tejo Santoso; Sarsono Sarsono; Istiqomah Istiqomah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
To find out the quality of employees at the Social Service in Wonogiri, the aspects used by researchers are by looking at work discipline, organizational culture, and communication. Quantitative method used in this research. Total population of 35 people. The sample used by all employees because it uses a saturated sample. This study uses SPSS assistance with data analysis techniques using instrument tests, normality tests, multicollinearity tests, heteroscedasticity, multiple linear regression analysis, t tests, F tests and tests of the coefficient of determination. First hypothesis (H1), it is concluded that discipline in work has a considerable influence on increasing the quality of human resources, with a significance of 2.236, organizational culture (H2) influences performance improvement. Communication (H3) in this study has the highest influence compared to the two previous variables with a resulting significance value of 3.302. Furthermore, testing simultaneously showed that all variables had a fairly high impact on improving the quality of human resources at the Wonogiri District Social Service.